The feasibility of the integrating of cycling in the road network of settlements - Lytvynenko, Т. P.; Smilyanets, L. V. (Видавництво Львівської політехніки, 2013)
In article are brought comparative features of the most wide-spread urban transport types. Are determined the positive changes, to which brings the development of bicycle moving in populated point. Is justified including bicycle infrastructure in the road network of populated point.
Keywords: cycling; bicycle infrastructure; road network; the individual ecological types of transport; settlement